Simulation of flow of the blade wind turbine - Tanasheva, N.K.; Shrager, E.R.; Dyusembaeva, A.N.; Kussaiynova, A.K.; Ospanova, D.A.; Bakhtybekova, A.R. (Publ.KarSU, 2016)
The paper is concerned with simulation of aerodynamics of a wind turbine blade in 3D space. The authors developed a grid model of the airspace in the form of an infinite cylinder wherein a wind turbine blade is arranged. The simulation made it possible to draw a picture of the cross-flow of a sail blade at various airflow rates. The investigators determined the pressure distribution pattern and distribution of the current lines in the symmetric plane for the angle of attack α=0° at an approach flow rate of 5 m/s.
Қысымның таралуын анықтаған желтурбина қалақшаларын орап ағудың көрнекілік моделі
Иллюстрационное моделирование обтекания лопасти ветротурбины с выявлением распределения давления
Keywords: Ansys Fluent; blade; flow pattern; simulation